WACANA KAMPANYE DALAM KAJIAN SEMANTIS - Rian Bromanggara; Aripudin ,; Larlen , (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2016)
ABSTRACT This research is a qualitative research with descriptive type. Sources of research data such as print media (newspapers / newspaper), and outdoor media (billboards, billboards, leaflets, banners, banners, posters, business cards, calendars) are mini-sized to a giant-sized plastered on the roadside and places general. Data analysis is the collection of campaign discourse data that exist in the public room, collecting sorting, classifying, and coding, and finding relationships to be included in the categories of types of meaning that exist in the data. Keywords: Discourse campaign, advertising, semantic